SAT0572 The Effect of Interleukin-4 on Mechanical Stress-Induced Protease Expressions by Human Chondrocytes. (10th June 2014) - Machida, T.; Nishida, K.; Hashizume, K.; Nakahara, R.; Ozawa, M.; Harada, R.; Ozaki, T.
Abstract : Background: We previously reported that runt-related transcription factor 2 (RUNX-2) has an important role in regulation of mechanical stress-induced expression of ADAMTS aggrecanases in chondrocytes. Interleukin-4 (IL-4) is an anti-inflammatory cytokine, like IL-10 and IL-13, which is known to suppress pro-inflammatory cytokine production and activities. In osteoarthritis (OA) synovial tissue, IL-4 inhibits the production of tumor necrosis factor-α and IL-1β. Local overexpression of IL-4 protects cartilage from metalloproteinase (MMP)-induced destruction by preventing the activation of pro-MMPs during immune complex-mediated arthritis. More recently, we reported that intra-articular injection of IL-4 ameliorates subsequent destruction of cartilage in instability-induced OA in rat knee joints. Objectives: To examine the effect of IL-4 on mechanical stress-induced expression of catabolic proteases by human chondrocytes. Methods: Normal Human Articular Chondrocytes from knee joint were purchased from Lonza (Walkersville, MD, USA). IL-4 was purchased from CHEMICON International, Inc. (Temecula, USA). Cells were cultured at 37°, and were seeded onto type II collagen coated stretch chambers. They were transferred to serum-free medium with or without IL-4 (10ng/ml) for 12h before cyclic tensile strain (CTS), and a uni-axial CTS (0.5 Hz, 10% elongation) was applied for 30 min using the ST-140 mechanical stretch system (STREX, Osaka, Japan). RNA was isolated at 1, 6, 12, 24h after CTS, reverse transcribed, and the expression of ADAMTS-4, -5, -9, MMP-13, and RUNX-2 examined by real-time PCR. Results: CTS induced the expression of ADAMTS-4, -9, MMP-13 at 24h, and MMP-3 at 6h after CTS in control samples. In IL-4 treated samples, the expression of ADAMTS-4, -5, -9, MMP-13 and RUNX-2 were significantly downregulated. ADAMTS-5 gene expression was biphasic (1h and 12h after CTS) in control samples, and both peaks (RUNX-2 dependent peak and cytokine dependent peak) were reduced in IL-4 treated samples. The concentration of IL-1β in the supernatant increased in control samples at 6h after CTS, but decreased in IL-4 treated samples. Conclusions: IL-4 treatment effectively suppressed the mechanical stress-induced expression of ADAMTS-4, -5, -9 and MMP-13, presumably by inhibition through RUNX-2 pathways. These data suggest the clinical chondro-protective effects of IL-4 against mechanical stress-induced cartilage degeneration. References: Tetsunaga T, Nishida K, Furumatsu T, Naruse K, Hirohata S, et al.Regulation of mechanical stress-induced MMP-13 and ADAMTS-5 expression by RUNX-2 transcriptional factor in SW1353 chondrocyte-like cells. Osteoarthritis Cartilage 2011; 19: 222-232. Goldring MB: The role of the chondrocyte in osteoarthritis. Arthritis Rheum 2000; 43: 1916-1926. Bendrups A, Hilton A, Meager A and Hamilton JA: Reduction of tumor necrosis factor alpha and interleukin-1 beta levels in human synovial tissue by interleukin-4 and glucocorticoid. Rheumatol Int 1993; 12: 217-220. Yorimitsu M, Nishida K, Shimizu A, et al: Intra-articular injection of interleukin-4 decreases nitric oxide production by chondrocytes and ameliorates subsequent destruction of cartilage in instability-induced osteoarthritis in rat knee joints. Osteoarthritis Cartilage 16(7): 764-71, 2008 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4837